In vitro and in vivo survival of mouse morulas and blastocysts following vitrification in 45% glycerol - Bertolini, Marcelo; Lange, Mateus da Costa; Rodrigues, José Luiz (Acta Scientiae Veterinariae, 2018)
The toxicity of cryoprotectant agents is one of the critical factors for the successful vitrification of mammalian embryos, which depends on the concentration, time and temperature of exposure to the cryoprotectant. Moreover, embryos from different species or stages of development have distinct levels of tolerance to cryoprotectant agents. This study aimed to evaluate the in vitro and in vivo survivals of mouse embryos after distinct times of exposure to two cryoprotectant concentrations prior to vitrification. In Experiment 1, compact morulas, blastocysts and expanded blastocysts were exposed to 10% glycerol for 10 min (group 1) or to 25% glycerol for 10, 5 and 2.5 min (groups 2, 3, and 4, respectively) prior to their exposure to the vitrification solution containing 45% glycerol for 1 min at 20°C before immersion in liquid nitrogen. Embryos were thawed in a water bath at 20°C for 20 sec, and the cryoprotectant was diluted in 1 M sucrose for 10 min. Then, embryos were morphologically evaluated following in vitro culture for 1 and 48 h. In vitro survivals of compact morulas and blastocysts were not affected by glycerol concentration and/or equilibration time prior to vitrification. However, expanded blastocysts demonstrated a lower survivability to vitrification. In Experiment 2, fresh and vitrified (according to procedures in group 1, Experiment 1) compact morulas and blastocysts were transferred to recipients following in vitro culture for 1 h at room temperature. Pregnancy rates, based on the proportion of viable fetuses, were similar between vitrified and fresh compact morulas (27% and 33%, respectively). However, vitrified blastocysts demonstrated a lower in vivo survival than controls (9% vs. 52%, respectively).